Culture and context: exploring attributions and caregiving approaches of parents of children with an intellectual disability in urban India. Issue 2 (24th February 2016) - John, Aesha; Bailey, Lucy E.; Jones, Jennifer L.
Abstract: We utilized a sociocultural lens and a qualitative approach to examine causal attributions and caregiving approaches of parents of children with an intellectual disability in a mid‐sized Indian city. Sixteen mothers and three fathers participated in a semi‐structured interview. Findings elucidate participants' active processing of the cause of their child's intellectual disability. They seemed to simultaneously draw upon religious, biological and situational factors to construct an explanation. As far as caregiving approaches, most parents reported moving away gradually from mainstream medicine to alternative medicine and physiotherapy and from regular education settings to special schools. The themes highlight the role of sociocultural factors and also cross‐cultural similarities in parental causal attributions and caregiving approach. The findings are discussed in the context of implications for social work practice and policy in India.